Geração de trombina em cães com hiperadrenocorticismo endógeno - Mora, Silvia Eugenia Vargas [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The hypercoagulable state is a serious condition that can lead to thrombosis and/or disseminated intravascular coagulation. Several diseases are associated with its development; however, conventional coagulation tests are unable to detect thrombotic risk. For the past few years, the thrombin generation test (TGA) has become one of the most studied methods for evaluating global hemostasis. Hyperadrenocorticism (HAC) is a common canine endocrinopathy that have been associated with hypercoagulability. However, the pathophysiological mechanisms are diverse and some of them are still misunderstood. The objective of this study was to evaluate the applicability of TGA for detecting compatible alterations with a hypercoagulable tendency and to correlate with an hemostatic profile comprised of fibrinogen, antithrombin (AT), D-dimer, prothrombin time (PT) activated partial thromboplastin time (aPPT), and routine laboratory tests for elucidating possible prothrombotic mechanisms. The majority of dogs (80.6%) presented at least one alteration of the hemostatic profile and/or TGA parameters. TGA at high concentration of activator showed significantly higher ETP (P= 0.0239) and peak (P= 0.0281) in Cushing patients. Fibrinogen (P = <0.0001) and AT (P = 0.0444) activity were significantly higher in the HAC group, while PT (P = 0.0046) and aPTT (P = 0.0002) were lower. Basal cortisol levels correlated positively with fibrinogen levels (r = 0.4503; P = 0.0355) and negatively with AT values (r = -0.4580; P = 0.0280). Fibrinogen and hematocrit values showed a negative correlation (r = -0.4853; P = 0.0076). Our study showed that dogs with HAC presented higher thrombin generation, however, TGA performed with lower concentrations of tissue factor were inadequate for assessing hypercoagulability. Degree of hypercortisolism influences AT and fibrinogen levels. Proteinuria does not appear to determine AT activity and dogs with HAC showed a significantly shortened PT and aPTT.

O estado de hipercoagulabilidade é uma condição grave que pode levar a um quadro de trombose e/ou coagulação intravascular disseminada. Diversas doenças estão associadas com seu desenvolvimento, porém, os exames de hemostasia convencionais são pouco sensíveis na detecção do risco trombótico. Um dos testes mais estudados nos últimos anos é a geração de trombina, método que consegue avaliar o potencial endógeno da hemostasia global. O hiperadrenocorticismo (HAC) é uma endocrinopatia de ocorrência comum em cães que pode desencadear um estado de hipercoagulabilidade secundária ao hipercortisolismo. Os mecanismos fisiopatológicos são diversos e alguns deles ainda não são bem compreendidos. O objetivo deste estudo foi avaliar a aplicabilidade do teste de geração de trombina (TGT) para detectar alterações compatíveis com hipercoagulabilidade em cães com hiperadrenocorticismo endógeno, assim como correlacionar com um perfil hemostático compreendido por fibrinogênio, antitrombina (AT), dímero-D, tempo de protrombina (TP), tempo de tromboplastina parcial ativada (TTPa), e exames gerais de rotina para desvendar possíveis mecanismos protrombóticos. A maioria dos cães apresentou pelo menos uma alteração no perfil hemostático e/ou TGT. O TGT realizado em altas concentrações de fator tissular mostrou incremento de ETP (P= 0.0239) e peak (P= 0.0281) nos cães com HAC. O fibrinogênio (P = <0.0001) e AT (P = 0.0444), apresentaram um aumento significativo no grupo com HAC, e o TP (P = 0.0046) e TTPa (P = 0.0002) uma diminuição. Os níveis basais de cortisol se correlacionaram de forma positiva com os níveis de fibrinogênio (r = 0.4503; P = 0.0355) e de forma negativa com os níveis de AT (r = -0.4580; P = 0.0280). O fibrinogênio e o hematócrito se correlacionaram negativamente (r = -0.4853; P = 0.0076). O estudo mostrou que os cães com HAC endógeno apresentam uma maior geração de trombina, no entanto, o TGT realizado com baixa concentração de fator tissular não foi adequada para detectar essas alterações. O grau de hipercortisolemia influencia os níveis de AT e fibrinogênio. A proteinúria parece não determinar os níveis de AT e os cães com HAC mostraram uma diminuição do TP e TTPa.
Thrombin generation in dogs with naturally occurring hyperadrenocorticism
Keywords: Hipercoagulação; Hemostasia; Trombose; Hipercortisolemia; Canino; Hypercoagulability; Hemostasis; Thrombosis; Canine; Hypercortisolism